Sediment Deposition Analysis using InfoWorks ICM for Segamat River, Muar River Basin - Liew, Yuk San; Safari Mat Desa,; Mou Leong Tan,; Chun Kiat Chang, (International Journal of Integrated Engineering, 2025)
Various environment-related issues within a river system associated with urbanization will lead to urban channel and river bank erosion and sedimentation problems such as floods, water quality degradation and disruption to the ecosystem. Apart from the development, river dredging activities and sand mining will also cause instability problems to the river morphology.  In view of its negative impacts to the river system, an assessment on the river morphology for Segamat River, Johor has been conducted.  The study aimed to examine the processes of erosion and deposition of river morphology and propose strategic measures to minimize the effects of erosion and sedimentation along the river.  Sediment transport modelling has been carried out for 10-, 50-, 100- and 1000-year Average Recurrence Interval (ARI) storm events based on the runoff hydrograph using InfoWorks Integrated Catchment Modelling (ICM) coupled with a sediment-transport module. The Ackers-White sediment transport equation was selected in the model due to its applicability across a wide range of particle sizes and flow conditions, offering reliable predictions for the study reach. The simulation results highlight the large variability in channel morphology along river reach, where the sediment transport model predicts more sediment deposition at the middle reach of Segamat River.  The findings underpin an Erosion and Sedimentation Control Plan (ESCP) that spatially targets dredging moratoria, buffer-zone restoration, and adaptive sand-extraction scheduling to restore morphodynamic equilibrium and reduce flood risk.